Metro Manila's best restaurants 1994 - The Philippine Tatler (Hongkong Illustrated Magazine Publishing, 1994)
"This first edition of Metro Manila's Best Restaurants 1994 is a guide to the finest food in the Philippines. Restaurants were nominated by leading figures in the food and wine industry, and by votes from thousands of members of the Cheese Club, La Chaine des Rotisseurs and the Philippine Chamber of Commerce. This is fascinating part of the world, historically, and the variety influences has percolated into the food. It makes valid observations about the growing interest in wine in the Philippines. The wine chart has been specifically aimed at those who are less familiar with this beverage and every review contains both a separate comment on, and rating of, available wines. There are nine pages of maps which will help locate the restaurants especially as they include visual landmarks by which one can plot one's course."
Keywords: Restaurants -- Philippines -- Manila Metropolitan Area